PERAN PEMERINTAH THAILAND DALAM MEREALISASIKAN GASTRODIPLOMASI THAILAND DI NEW ZEALAND TAHUN 2005 - 2010 - Tri Huliyani; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Gastrodiplomacy is part of public diplomacy and cultural diplomacy that uses food as a media of cross-cultural communication. Thai Gastrodiplomacy was officially issued by the Government of Thailand in 2002. New Zealand has become one of the destinations for Thai Gastrodiplomacy due to the historical factor of good relations between the two since 1956 and the increasing number of Thai people in New Zealand. In 2005, bilateral relations between the two countries increased after the TNZCEP was agreed which indirectly supported the implementation of Thai gastrodiplomacy in New Zealand. This research was conducted to find out the role of the Thai Government in impementing its gastrodiplomacy in New Zealand during 2005 to 2010. In this study, the authors used a qualitative methods, with data collection techniques through literature studies sourced from books, journals, theses, and websites. as well as emails to the relevant Thai government. Researchers also uses the perspective of constructivism, soft power theory and gastrodiplomacy concept. The results of this study show that the Government of Thailand is carrying out its role through programs that are made in the gastrodiplomacy strategy as follows; gastrodiplomacy campaign, product marketing strategy, food events strategy, coalition-building strategy, media relations strategy, and education strategy carried out in New Zealand during the period 2005-2010 time. Keywords: Gastrodiplomacy, TNZCEP, Perspective of Constructivism